2020
DOI: 10.1155/2020/6025452
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Strengthening and Sealing Materials and Their Application in Coal Mines

Abstract: To solve the problem of unstable sealing in the sealing section of a gassy, soft coal seam, a seal reinforcement material for gas extraction boreholes was developed, which was mainly made of ordinary Portland cement and blended with additives such as aluminium powder, quicklime, and gypsum. Firstly, in order to obtain the necessary expansion and compressive strength of reinforcement material, key factors affecting the material properties were determined. Key factors affecting the expansion properties and compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…After the samples were first set into shape, and all samples will be divided into 3 groups of 5 samples each. Then, the grouting materials commonly used in coal mines were filled in the boreholes: polyurethane and expansion cement [ 46 , 47 ]. All samples were placed in a concrete standard curing box for 28 days, and then the surfaces of the samples were polished and repaired to ensure the dimensional accuracy and surface flatness of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…After the samples were first set into shape, and all samples will be divided into 3 groups of 5 samples each. Then, the grouting materials commonly used in coal mines were filled in the boreholes: polyurethane and expansion cement [ 46 , 47 ]. All samples were placed in a concrete standard curing box for 28 days, and then the surfaces of the samples were polished and repaired to ensure the dimensional accuracy and surface flatness of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Wei et al (2020) investigated the sealing characteristics of aircraft Glacis rings under 21 MPa operating conditions, and the results showed that the friction force gradually increased with the increase of fluid pressure; the friction force increased significantly with the increase of temperature. Yan et al (2020) considered the amplitude and wavelength of surface roughness and analyzed the effects of ACGT-type seal motion velocity and hydraulic oil viscosity variation on the lubrication performance and sealing performance of the seal. Zhang et al (2021) and Zhang and Li (2021) conducted numerical analysis and finite element simulation research on the main seal of aviation actuators, established a mixed lubrication model for reciprocating seals, calculated the friction force and reverse pump return rate of the reciprocating seal system and provided a reference basis for the structural optimization of reciprocating seals.…”
Section: Introductionmentioning
confidence: 99%
“…China's coal seams have complex and variable endowment conditions, and mines are prone to serious gas disasters [1][2][3][4]. In the process of gas management, the hole formation quality of a gas extraction borehole is an important factor in determining the efficiency of gas extraction [5][6][7][8][9]. Under the influence of ground stress and mining, gas extraction boreholes are prone to collapse and deformation, which seriously affects gas management [10,11].…”
Section: Introductionmentioning
confidence: 99%